Selected Biomechanical Variables and Their Relationship with the Accuracy Index of the Forehand Topspin Stroke Among Table Tennis Players of Khanaqin Sports Club - Hassan, Azad Ali (Indonesian Journal Publisher, 2025)
Table tennis is considered one of the sports with high physical demands, requiring a set of precise motor skills such as speed, strength, and accuracy to execute movements proficiently. Among the most prominent skills that a player needs to master in this game are the forehand and backhand spin shots, which require a high level of coordination among various biomechanical forces that control the player's motor performance. Problem of the Study: The main scientific problem is that traditional tests used to measure the accuracy of spin shots often rely solely on analyzing the ball's landing area, without considering the time taken to execute the shot, even though time is a critical factor that can directly affect the effectiveness and accuracy of performance. Hence, there is a need to adopt a new research perspective that considers the integration of racket angle, shot execution time, and ball trajectory as a methodological approach to developing more accurate and objective assessment tools. The researcher have adopted biomechanics as a means to achieve the following objectives: 1. To determine the accuracy index of forehand and backhand spin shots for players from Khanqin Sports Club in table tennis. 2. To explore the relationship between some biomechanical variables (racket angle and ball launch speed) and the accuracy index of forehand and backhand spin shots, aiming to identify how these variables affect performance. Hypothesis of the Study: There is a statistically significant relationship between some biomechanical variables (racket angle and ball launch speed) and the accuracy index of forehand spin shots for players from Khanqin Sports Club in table tennis. This chapter includes the methodology used by the researcher. The researcher employed various means and tools to collect information and samples, defined as